Changes in salivary biomarkers of pain, anxiety, stress, and inflammation related to tooth movement during orthodontic treatment: a systematic review - Rodrigo RODRIGUES; Caio Melo MESQUITA; Helena Benatt do Nascimento ALVES; Filipe Gontijo SILVA; Walbert de Andrade VIEIRA; Paula Cristiana Santos de AGUIAR; Carlos FLORES-MIR; Luiz Renato PARANHOS; Rui Barbosa de BRITO-JÚNIOR (Dental Press Journal of Orthodontics)
ABSTRACT Objective: This systematic review aimed to analyze the literature on changes in endogenous salivary biomarkers of pain, anxiety, stress, and inflammation related to tooth movement during orthodontic treatment of children and adolescents. Material and Methods: An electronic search was performed in nine databases to identify quasi-experimental studies, without restricting publication language and year. Two reviewers extracted the data and assessed the individual risk of bias using the JBI tools, and the certainty of evidence using the GRADE tool. Results: The electronic search found 7,038 records, of which 12 met the eligibility criteria and were included in the qualitative synthesis. Most studies had a low risk of bias. Biomarkers were grouped into five categories: electrolytes, enzymes, hormones, immunoglobulins, and mediators. Electrolytes showed decreased Ca2+, Pi3+ and K+ levels, and increased Na+ and Cl- levels. All enzymes (ALP, LDH, MMP8, and MMP9) increased over time. Hormones presented a decrease in leptin and some fluctuations in daily cortisol levels. Immunoglobulins (IgA, IgG, IgM, IgD, and IgE) had no significant changes, and salivary IgA showed divergent results among studies. Mediators (sRANKL, OPG, IL‐1β, and PGE2) showed fluctuations at different treatment stages, mainly after orthodontic activation. Conclusions: Based on a very low certainty level, orthodontic tooth movement had little to no effect on endogenous salivary biomarkers.